Understanding Li-Ion Battery Anode Degradation and Pore Morphological Changes through Nano-Resolution X-ray Computed Tomography. Issue 13 (1st January 2016) - Frisco, Sarah; Kumar, Arjun; Whitacre, Jay F.; Litster, Shawn
Abstract : Sophisticated electrode design for high power and energy density batteries will require a more thorough understanding of how electrode porosity affects cell failure mechanisms such as solid electrolyte interphase (SEI) formation. This study uses high resolution three dimensional (3D) mapping to examine the anode SEI deposits in off the shelf Li-ion cells that have been deeply cycled to complete failure. Scanning electron microscopy (SEM) was used to show the buildup of SEI on the surface of the graphite anode, while nano-scale resolution X-ray computed tomography (nano-CT) was used to show the SEI accumulation within the anode's pore structure. Through a combination of phase contrast and absorption contrast imaging, it was shown that the average pore diameter and total internal pore volume fraction decreased significantly after cycling, while there was a corresponding increase of absorption contrast from heavier elements throughout the anode. We propose this is due to buildup of electrolyte decomposition products within the pores.